Implementasi Pembebasan Biaya Jasa Notaris bagi Masyarakat Tidak Mampu di Kabupaten Boyolali - Agung Nugroho; Hari Purwadi; Erna Dyah Kusumawati (Jurnal Hukum Lex Generalis, 2025)
The notary’s obligation to provide free services for underprivileged citizens is a normative mandate of the Notary Office Law, emphasizing the notary’s social function as a public official and promoting access to justice for vulnerable groups. This study examines the implementation of pro bono notary services in Boyolali Regency using an empirical juridical approach that combines normative legal analysis with field interviews. Findings show that most notaries understand this obligation, yet verification mechanisms for determining low-income status vary. Such inconsistencies risk inequality. The Regional Supervisory Council must strengthen oversight through standardized procedures, institutional support, and accountability improvements to ensure consistent pro bono service delivery.